A Characterization of Virgin Coconut Oil Obtained via Extraction Utilizing Tamarind Seed Skin Waste - Ilyas, Muhammad Ali; Multazam, Ahmad; Hidayatulloh, Alpiana; Fajri, Nefi Andriana (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This study aims to provide a characterization of virgin coconut oil obtained through the acidification method, using tamarind seed skin as an oil extractor. The utilization of tamarind seeds is motivated by the fact that they are considered a waste product and are not commonly used by the community. Additionally, tamarind seeds contain organic acids, such as citric acid, tartaric acid, and malic acid, which can effectively hydrolyze the bond between oil and other substances in coconut flesh, such as proteins and carbohydrates. The characterization of virgin coconut oil includes a range of tests, such as organoleptic evaluation, density measurement, moisture content determination, free fatty acid analysis, and peroxide number determination, which are compared to coconut oil produced through heating. The virgin coconut oil is extracted from grated coconut flesh by mixing tamarind seed skin, which has been mashed, with grated coconut flesh in a 1:4 ratio. This mixture is then homogenized and incubated for approximately 10 minutes to extract the oil. The organoleptic evaluation results of the virgin coconut oil produced through acidification demonstrate a light yellow color with no detectable taste or odor, while the coconut oil produced through heating has a dark yellow color, a slightly rancid smell, and a distinct coconut oil taste. The density of the virgin coconut oil produced through acidification and heating is 0.870 g/mL and 0.868 g/mL, respectively. The moisture content of the virgin coconut oil produced through acidification and heating methods is 0.1713% and 0.1700%, respectively. The free fatty acid content for the acidification and heating methods is 0.14% and 3.252%, respectively. The peroxide number test shows that the acidification method yields a higher value of 27.41 meq O2 / kg compared to 5.694 meq O2 / kg for heating.